Disruption of ABI4 Enhances Anthocyanin Accumulation in Arabidopsis Seedlings Through HY5-Mediated Light Signaling - Mingyang Zeng; Yan Wu; Shunfa Lin; Fang Zhang; Haiyan Jiang; Lixia Ma; Dong Liu (Plants, 2025)
The AP2/ERF transcription factor ABSCISIC ACID INSENSITIVE 4 (ABI4) plays diverse roles in plant development and responses to abiotic stress. However, its potential involvement in regulating anthocyanin biosynthesis is not fully understood. In this study, three different loss-of-function abi4 alleles (abi4-1, abi4-2, and abi4-101) were employed to investigate the role of ABI4 in the regulation of anthocyanin accumulation in Arabidopsis seedlings. These abi4 mutants exhibited significantly increased anthocyanin accumulation, which was associated with elevated expression of genes involved in anthocyanin biosynthesis. HY5 (LONG HYPOCOTYL 5), a central component of photomorphogenesis, acts as a key light-regulated molecular switch. Further analysis revealed that ABI4 requires HY5 to function as a negative regulator of anthocyanin biosynthesis. Additionally, loss of ABI4 resulted in heightened light sensitivity, leading to increased light-induced chlorophyll accumulation and chloroplast development, along with upregulation of photosynthesis-related genes. Interestingly, the light-hypersensitive phenotype of abi4 mutants was partially rescued by the loss of HY5 function. Taken together, these findings demonstrate that ABI4 negatively regulates anthocyanin accumulation in Arabidopsis seedlings through a HY5-dependent light signaling pathway.